Comparative Study of Optical Response of Semiconductors Using FDTD Method - ., Anushka; Aruna Priya, P (International Journal of Engineering and Technology, 2018)
Materials exhibit different properties at nanoscale than at visible-scale due to predominance of quantum effects. For solar cell applications, a nanostructure of particular interest is the nanowire. Free and open-source FDTD (Finite-Difference Time-Domain) software is used to simulate and study optical response of semiconductor materials both in the absence and presence of metal nanowires in 400 nm - 500 nm wavelength range. The results indicate enhancement in optical response of semiconductors in the presence of nanowires. Best enhancement for silicon can be obtained by using combinations of silver and gold nanowires, and this result can be used to improve the efficiency of solar cells.Â Â